Influence of interpersonal violence on maternal anxiety, depression, stress and parenting morale in the early postpartum: a community based pregnancy cohort study - Malta Lise A; McDonald Sheila W; Hegadoren Kathy M; Weller Carol A; Tough Suzanne C (BMC, 2012)
Abstract Background Research has shown that exposure to interpersonal violence is associated with poorer mental health outcomes. Understanding the impact of interpersonal violence on mental health in the early postpartum period has important implications for parenting, child development, and delivery of health services. The objective of the present study was to determine the impact of interpersonal violence on depression, anxiety, stress, and parenting morale in the early postpartum. Methods Women participating in a community-based prospective cohort study (n = 1319) completed questionnaires prior to 25 weeks gestation, between 34-36 weeks gestation, and at 4 months postpartum. Women were asked about current and past abuse at the late pregnancy data collection time point. Postpartum depression, anxiety, stress, and parenting morale were assessed at 4 months postpartum using the Edinburgh Postnatal Depression Scale, the Spielberger State Anxiety Index, the Cohen Perceived Stress Scale, and the Parenting Morale Index, respectively. The relationship between interpersonal violence and postpartum psychosocial health status was examined using Chi-square analysis (p < 0.05) and multivariable logistic regression. Results Approximately 30% of women reported one or more experience of interpersonal violence. Sixteen percent of women reported exposure to child maltreatment, 12% reported intimate partner violence, and 12% reported other abuse. Multivariable logistic regression analysis found that a history of child maltreatment had an independent effect on depression in the postpartum, while both child maltreatment and intimate partner violence were associated with low parenting morale. Interpersonal violence did not have an independent effect on anxiety or stress in the postpartum. Conclusion The most robust relationships were seen for the influence of child maltreatment on postpartum depression and low parenting morale. By identifying women at risk for depression and low parenting morale, screening and treatment in the prenatal period could have far-reaching effects on postpartum mental health thus benefiting new mothers and their families in the long term.